Voices from the Frontlines: The Challenges and Rewards of Immigration Activism. (November 2022) - Velez, Brandon L.; Baranowski, Kimberly A.; Manosalvas, Kiara
This consensual qualitative research study explored immigration activists' perspectives on the rewards and challenges of their work, how they cope with challenges, and their recommendations for how psychologists could best support them. Fifteen self-identified immigration activists completed one-hour, semi-structured, individual interviews. Analysis yielded 25 categories associated with six domains (Catalysts for Activism; Vision for Activism; Rewards; Challenges; Coping Strategies; and Recommendations for Psychological Practice, Research, and Advocacy). Participants reported emotional distress and burnout, but this challenge co-occurred with rewards such as connecting with colleagues or increased skills and tools. Activists used a variety of coping strategies, including maintaining boundaries, and encouraged psychologists to provide them with psychoeducational training, to provide services that are relevant and accessible to immigrant communities, and to advocate for immigration issues. The findings are placed in context with prior research pertaining to social identity, social justice activism, and multicultural competence.